Shell side plain tube bundle performance of a multi-pass direct expansion evaporation of ammonia at various degrees of exit superheat. (June 2017) - Abbas, Ahmad; Ayub, Zahid H.; Ayub, Adnan H.; Khan, Tariq S.; Chattha, Javed A.
Highlights: Direct expansion of ammonia on shell side of a shell and tube evaporator. Low charge systems. Bundle effect in a multi-tube evaporator. Abstract: This paper presents the experimental results of shell side dry expansion evaporation characteristics of ammonia on a triangular pitch plain tube bundle in a multi pass cross flow configuration evaporator. Heat exchanger had 4 passes with 3 plain tubes in each pass. The average bundle heat transfer coefficient showed better performance at −1.7 °C versus −20 °C. Heat transfer performance of individual passes were studied at saturation temperature of −1.7 and −20 °C, heat flux range of 5 to 45 kW m −2 and exit superheat temperature of 2 to 10 °C. Present data suggest that variation in bundle performance is less significant at lower heat fluxes with low degree of exit superheat. Top pass with maximum quality along the bundle height showed the least performance with increase in the degree of exit superheat.